A Study of the Challenges and design perspectives Affecting Physical Computing Teaching and Digital Education - Mohanna, Mohammed Hani (Journal of Humanities & Social Sciences, 2019)
The shift towards physicality and materiality in interaction design and the rise of the Internet of Things is likely to lead to a high demand for physical computing devices and experiences in the coming years. Previous researches have argued that design and development for physical computing require on a diversity of skills including physical design, electronics, computational logic and programming and collaboration. Recent trends in computing education (e.g., initiatives that seek to encourage engagement with computer science topics from a younger age) have the potential to make schools a highly promising site for the development of physical computing skills. Yet, we hypothesize that teaching and learning physical computing is likely to present a range of unique challenges that aren’t addressed by programs that are primarily focused on topics of computing and computer programming alone. In this paper, we present a study that explores the extent and nature of physical computing teaching in the context of one high-profile computing education program: the UK’s Computing at School initiative. Our study comprised a questionnaire that was distributed to teachers, and follow-up interviews with selected respondents. Our findings suggested that physical computing concepts aren't commonly taught in schools, despite physical computing tools being prevalent.
Keywords: Physical computing; learning by doing; games and gamification; computing at schools; electrical circuits